P2X7R-NEK7-NLRP3 Inflammasome Activation: A Novel Therapeutic Pathway of Qishen Granule in the Treatment of Acute Myocardial Ischemia - Li Y; Sun X; Liu X; Li J; Li X; Wang G; Liu Y; Lu X; Cui L; Shao M; Wang Y; Wang W; et al. (Dove Medical Press, 2022)
Yanqin Li,1,* Xiaoqian Sun,1,* Xiangning Liu,1,* Junjun Li,2 Xuan Li,1 Gang Wang,1 Yizhou Liu,1 Xiangyu Lu,2 Lingwen Cui,2 Mingyan Shao,3 Yong Wang,1,3,4 Wei Wang,1,4,5 Chun Li2,4 1College of Chinese Medicine, Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China; 2Modern Research Center for Traditional Chinese Medicine, School of Chinese Medicine, Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China; 3School of Life Sciences, Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China; 4Beijing Key Laboratory of TCM Syndrome and Formula, Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China; 5Guangzhou University of Chinese Medicine, Guangdong, 510006, People's Republic of China*These authors contributed equally to this workCorrespondence: Wei Wang, Guangzhou University of Chinese Medicine, Guangdong, 510006, People's Republic of China, Tel +86 13910026960, Email wangwei26960@126.com Chun Li, Modern Research Center for Traditional Chinese Medicine, School of Chinese Medicine, Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China, Tel +86 15810068615, Email lichun19850204@163.comBackground: Acute myocardial ischemia (AMI) is a common heart disease with increasing morbidity and mortality year by year. Persistent and sterile inflammatory infiltration of myocardial tissue is an important factor triggering of acute myocardial ischemia secondary to acute myocardial infarction, and NLRP3 inflammasome activation is an important part of sterile inflammatory response after acute myocardial ischemia. Previous studies have shown that Qishen granule (QSG) can significantly inhibit the inflammatory injury of myocardial tissue caused by ischemia, but its effect and specific mechanism of inhibiting the activation of NLRP3 inflammasome have not been reported. This study was to investigate the specific mechanism of QSG inhibiting inflammation after AMI, and to validate the possible targets.Methods: The myocardial ischemia model in mice was established by ligation of the left anterior descending coronary artery. Echocardiography was used to evaluate the cardiac function of the mice. Plasma CK-MB and cTnl were detected by ELISA to evaluate the degree of myocardial injury. The extent of myocardial tissue inflammation in mice was assessed by HE staining and immunohistochemistry of IL-18, IL-1β. The expressions of NLRP3, ASC, Caspase-1, and CD86 were detected by immunofluorescence; detection of key pathway proteins P2X7R, NEK7, NLRP3, ASC, Caspase-1, and effector proteins IL-18, IL-1β by Western blot. In vitro experiments, ATP+LPS was used to construct a RAW264.7 macrophage NLRP3 inflammasome activation model. Immunofluorescence and Western blot analysis were performed to detect the expression of NLRP3 pathway activator and effector proteins. Plasmid-transfected P2X7R overexpression and immunoprecipitation assays were used to evaluate the QSG-regulated NLRP3 inflammasome activation pathway.Results: QSG rescued cardiac function and further reduced inflammatory effects in mice by inhibiting NLRP3 inflammasome activation. In vitro, QSG inhibited LPS combined with ATP-induced NLRP3 inflammasome activation in RAW264.7 macrophages by downregulating the expression of NLRP3 inflammasome key pathway proteins. In addition, inhibition or overexpression of P2X7R in RAW264.7 macrophages and immunoprecipitated protein interactions further confirmed that QSG reduces macrophages inflammasome activation via the P2X7R-NEK7-NLRP3 pathway.Conclusion: P2X7R-NEK7-NLRP3 inflammasome activation is a novel therapeutic mechanism of QSG in the treatment of acute myocardial ischemia.Keywords: acute myocardial ischemia, inflammation, macrophages, P2X7R-NEK7, NLRP3 inflammasome, Qishen granule